A Systems study on the Materials Management Division of Metro, Inc. - dela Cuesta, Danny; Deligente, Ethel; Diesta, Relly; Kapunan, Medz; Nasayao, Celna; Pati, Estela; Pisang, Beth; Salazar, Tessa; Santos, Jorge; Tan, Mae (College of Engineering, 1985)
This study intends to apply the principles of Systems Analysis and Design to a real world situation and in the process blend practice and theory. The main objective of this study is to improve MMD by evaluating the present system, identifying possible problem areas and recommending alternative solutions to these problems. To attain the objective, the initial step is familiarization with the system, fact-finding, data gathering, identifying the activities undertaken and the rationale behind them from which the formulation of the problem proceeds. The group first took a look at the macrosystem, the Engineering Department of the Meralco Transit Organization, Inc. (METRO, Inc.). The Materials Management Division (MMD) was then isolated from the other divisions, being the system of interest. Linkages with the other divisions were identified. The system under study was analyzed according to the four (4) components of a system which are the following: People and Organization; Systems and Procedures; Tools, Equipment and Facilities, and; Information System. The group performed actual plant visits to become oriented with the present system, to define the system's main objective and to determine the system's boundaries and constraints. The group gathered data through direct observations, interviews, and analysis of relevant objectives. Furthermore, the group conducted a systems analysis to identify problem areas, to determine causes and effects of the problem, and to formulate alternative solutions to these identified problems. The group undertook the study from December 1984 to February 1985. Due to the limited time, the group therefore suggests that before implementation of the recommendations, a further study should be conducted. The following are the problems identified by the group: a) Unanticipated and recurring stock-outs, b) Erratic delivery of materials, c) Inefficient capability of coping with the work schedule, d) In application of inventory planning and control, e) Inadequate space and f) Poor working conditions.